1983
DOI: 10.1038/301674a0
|View full text |Cite
|
Sign up to set email alerts
|

Location and primary structure of a major antigenic site for poliovirus neutralization

Abstract: We have determined a major antigenic site for virus neutralization on the capsid protein VP1 of poliovirus type 3. Antigenic mutant viruses selected for resistance to individual monoclonal antibodies had point mutations concentrated in a region 277-294 bases downstream from the start of the region of viral RNA coding for VP1. These findings provide the basis for an improved understanding of the molecular basis of virus neutralization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
2

Year Published

1983
1983
2006
2006

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 192 publications
(103 citation statements)
references
References 35 publications
7
94
2
Order By: Relevance
“…The results of monkey neurovirulence tests on the plaquepurified virus stocks are shown in Table 1 in terms of paralysis and poliovirus-induced lesions of the brain and spinal cord. As expected, all the animals inoculated with the vaccine strain P3/Leon 12al b 41 I survived free from paralysis until site [28] day22, when they were sacrificed. This result in thc WHO neurovirulence test would pcrmit the rcleasc of this preparation as a vaccine.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The results of monkey neurovirulence tests on the plaquepurified virus stocks are shown in Table 1 in terms of paralysis and poliovirus-induced lesions of the brain and spinal cord. As expected, all the animals inoculated with the vaccine strain P3/Leon 12al b 41 I survived free from paralysis until site [28] day22, when they were sacrificed. This result in thc WHO neurovirulence test would pcrmit the rcleasc of this preparation as a vaccine.…”
Section: Resultssupporting
confidence: 77%
“…The TI oligonucleotide fingerprint of P3/Leon 12alb shows no differences from its neurovirulent progenitor among 55 well-characterized large oligonucleotides [28], suggesting a high degree of sequence homology, greater than that observed between the Sabin type 1 strain and its virulent progenitor Pl/Mahoney [29]. This was borne out by the sequences of the region encoding VPI.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The antigenic structure of poliovirus has been studied extensively, and several sites to which neutralizing antibodies bind have been identified by the isolation and characterization of antigenic variants (Minor et al, 1983(Minor et al, , 1986Diamond et al, 1985;Blondel et al, 1986;Page et al, 1988;Wiegers et al, 1989). The atomic structures of the type 1 strain Mahoney (Hogle et al, 1985) and the Sabin type 3 strain Leon 12alb (Filman et al, 1989) have been determined, and the antigenic sites have been shown to form apparently distinct structural features on the virus surface.…”
Section: Introductionmentioning
confidence: 99%
“…By using a variety of neutralizing monoclonal antibodies and analyses of neutralization-resistant mutants, the antigenic domains on poliovirus types 1 and 3 have been characterized and assigned to the 3D structure of the virus (Blondel et al, 1986;Diamond el al., 1985;Hogle et al, 1985;Minor et al, 1983Minor et al, , 1985Minor et al, , 1986van der Weft et al, 1983). By genetic engineering procedures chimeric poliovirus particles have been made that are infectious and immunogenic, raising the possibility that new types of vaccines may be produced by such procedures (Burke et at., 1988).…”
Section: Introductionmentioning
confidence: 99%